A nonlinear control algorithm for a wind turbine. Issue 6 (2nd November 2015) - Aimene, Merzak; Payman, Alireza; Dakyo, Brayima
Abstract : Purpose: – The purpose of this paper is to propose a new nonlinear control algorithm to control a wind turbine based on permanent magnet synchronous generator (PMSG) connected to the grid via a back-to-back converter. The control algorithm is composed of a flatness-based method for the machine side convertor (MSC) and a voltage-oriented method for the grid side converter (GSC). Design/methodology/approach: – For the MSC control, the output variable is chosen properly to prove that the system is flat at first. Then, the appropriate reference trajectories are planned on its components. The reference trajectories are such designed that the system operates in maximum power point tracking (MPPT) mode. Finally, state feedback regulators are used to force the system output to follow its reference. To control the GSC, a classical voltage-oriented control method is used. Findings: – The simulation results obtained with a random wind speed are presented in order to prove the validity of the proposed control algorithm. These results show that the system is controlled successfully while it operates in the MPPT mode or in its maximum power limitation mode. Originality/value: – In this paper, a new algorithm based on flatness property is presented to control a variable speed wind turbine based on a PMSG. The proposed control method allows the system to operate in optimal operating modes.